The Efficacy and Benefits of Yoga in Hematological Malignancies: A Systematic Review of Randomized Controlled Trials - Giridharan , S; Bhana, Rajanee (International Research Journal of Ayurveda & Yoga, 2024)
Introduction: Hematological malignancies, such as leukemia, lymphoma, and multiple myeloma, contribute significantly to global cancer morbidity and mortality. Patients often face high chemotherapy toxicity and significant physical and psychological symptoms. The use of yoga as a supportive care intervention has shown promise in alleviating these side effects and enhancing patients’ quality of life (QOL). Methods: Following Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines, a comprehensive literature search was conducted in PubMed, Scopus, Web of Science, and the Cochrane Library using specific keywords related to yoga and hematological malignancies. Studies from 2000 to 2023 that investigated the effects of yoga on physical or mental health outcomes in patients with hematological malignancies were included. Data extraction and synthesis were performed by two reviewers, focusing on study design, sample size, intervention details, outcome measures, and critical findings. The quality of studies was assessed using the Cochrane Risk of Bias tool. Results: The search yielded 903 items, with five randomized controlled trials meeting the inclusion criteria. These trials demonstrated that yoga intervention significantly reduced fatigue, emotional distress, and pain in patients with hematological malignancies. However, challenges related to the feasibility of online interventions and adherence were noted. Conclusion: Yoga interventions have the potential to significantly enhance the QOL for patients with hematological malignancies by mitigating fatigue, pain, and psychological distress. Further research is warranted to optimize these interventions and integrate yoga into comprehensive cancer care. Hematological malignancies, comprising a range of cancers including leukemia, lymphoma, and multiple myeloma, account for a substantial portion of global cancer diagnoses and fatalities. The incidence and prevalence of these malignancies have exhibited an upward trend over the years, posing significant public health concerns. They represent approximately 7% of all cancers and rank as the fourth most frequently diagnosed cancer in the western world.[1,2]